An Analysis of The Influences of Kumon Learning Method Toward The Learning of English as A Foreign Language - Farani, Maya Anisa; Farmasari, Santi; Isnaini, Muh. (Program Studi Pendidikan Bahasa Inggris, 2024)
Seeing the fact that English began to be used as an international language and children began to learn it, Kumon Learning Institute began to develop English lessons called EFL (English as a Foreign Language). However, the different influence of Kumon Learning Method toward the learning of English as a Foreign Language to the existing students and new students remain questionable. The purpose of the study is to identify and describe the different influence of Kumon Learning Method toward the learning of English as a Foreign Language between the existing students and new students. The reasearcher used descriptive qualitative approach to support this research. The population of this research is English as a Foreign Language students in Kumon Sweta which consist of 29 students, and all of them were taken as samples. In this research, data was collected by observation and interview. The data was analyzed using the theory from Miles and Huberman (2014), started from data collection, data reduction, data display, and conclusion drawing/verifying. The research showed that there are differences in the influence of Kumon learning method toward the learning of English as a foreign language to the existing and new students. The differences include language skills, study habits, confidence, independence, and progress and skill development. Additionally, both existing and new students can experience boredom because of various factors such as different preferences and learning styles, so it cannot be classified at certain times. The implication of this research is the need for an approach between teachers and students to be able to determine learning programs that are appropriate to students' abilities and learning styles, so as not to have a negative impact on the learning process.